Addressing private practice in public hospitals - Xidong Guo; Sarah Parlane (University College Dublin, UCD Centre for Economic Research, 2020)
This paper proposes a theoretical analysis of the private provision of care within public hospitals and assesses its impact on the quality and cost of healthcare. We also capture this policy's impact on the number of outpatients that are seen and the number that are cured. We show that the private income gathered by consultants engaged in dual practice has a negative impact on the level of care being provided as it incentivises consultants to focus on the number of patients seen. However, the private fees generate lower healthcare costs. Hence the removal of private practice in public hospitals is only optimal when the benefit associated with curing patients is large enough. The impact on waiting lists is ambiguous. Considering that consultants may differ in their ability, we show that the optimal contracts enable senior doctors (with more experience) to get a greater private income than junior doctors when discrimination between senior and junior physicians is allowed. When discrimination is not allowed, it is optimal to offer a uniform contract. Proposing distinct contracts, as currently done in Ireland, increases healthcare costs due to incentive compatibility issues.
Keywords: D86; I11; I18; L32; 330; Healthcare; public hospital; dual practice; optimal contracts and consultant's incentives